Flood in Kelantan. - Chan, Ngai Weng (Universiti Sains Malaysia, 2016)
The December 2014 flood in Kelantan caused significant loss of life,infrastructure destruction, Property damage,crop loss,loss of livelihoods,losses in healthcare etc.victims experienced both direct and indirect,as well as tangible and intangible losses.